Dual random lattice modeling of backward erosion piping. (January 2019) - Fascetti, Alessandro; Oskay, Caglar
Abstract: This manuscript provides a novel random lattice model to simulate the progressive degradation of soil embankments induced by the backward erosion piping (BEP) phenomenon. The progressive evolution of the piping process is described by expressing apparent diffusivity of the soil as a function of the local hydraulic gradient. In order to accurately compute local field gradients, a dual lattice approach that evaluates the response on both Delaunay and Voronoi nodes is formulated. The response computed at the Delaunay nodes is then employed to augment field gradient computation on the Voronoi grid. The proposed dual lattice model is numerically verified and validated by comparing numerical results with BEP experiments available in the literature.